Cerebral Vasoreactivity Changes Over Time in Patients With Different Clinical Manifestations of Cerebral Small Vessel Disease - Staszewski, Jacek; Dȩbiec, Aleksander; Skrobowska, Ewa; Stȩpień, Adam (Frontiers in Aging Neuroscience, 2021)
Objectives: Endothelial dysfunction (ED) has been implicated in the pathogenesis of cerebral small vessel disease (SVD). The aim of this study was to evaluate ED and cerebrovascular reactivity (CVR) in patients with different manifestations of SVD, with similar and extensive radiological burdens of SVD, compared with a control group (CG) with normal MRI matched for age, gender, hypertension and diabetes and to evaluate the change of CVR following 24 months. Methods: Vasomotor reactivity reserve (VMRr), breath-holding index (BHI) of the middle cerebral artery were measured with transcranial ultrasound techniques in 60 patients (20 in the each group) above 60 years with extensive white matter lesions (WMLs, Fazekas grade≥2) with history of lacunar stroke, vascular dementia or parkinsonism, and 20 individuals from CG. Results: The mean age, sex distribution, prevalence of the main vascular risk factors were similar in patients with SVD and CG. VMRr (56.7±18%) and the BHI (0.82±0.39) were more severely impaired at baseline and at follow-up (respectively, 52.3±16.7% and 0.71±0.38) in the SVD patients regardless of the clinical manifestations (ANOVA, p>0.1) than in the CG (respectively, baseline VMRr 77.2±15.6%, BHI 1.15±0.47, p<0.001; follow-up WMRr 74.3±17.6%, BHI 1.19±0.4, p<0.001). All assessed CVR measures (VMRr and BHI) significantly decreased over time in subjects with SVD (Wilcoxon signed-rank test p=0.01), however, there was only a trend toward decreased VMRr in CG (p=0.08) and no significant change in BHI over 24 months of observation (p=0.12). Conclusions: Our study provided further evidence that cerebral endothelial dysfunction occur in patients with different clinical manifestations of SVD. We also demonstrated that change in CVR measures is detectable over a 24 months follow-up period. CVR reactivity measures decreased over time in subjects with SVD with a trend toward VMRr decrease in subjects without SVD but with similar atherothrombotic risk factors.